Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(=5\left(x^2-6x+9-4y^2\right)\)
=5(x-3-2y)*(x-3+2y)
Ta có:
a) 5x - 20y = 5(x - 4y)
b) 5x(x - 1) - 3x(x - 1) = x(x - 1)2
c) x(x + y) - 5x - 5y = x(x + y) - (5x + 5y) = x(x + y) - 5(x + y) = (x - 5)(x + y)
d) x2 - 9 = (x - 3)(x + 3)
e) 42 - 25 = (4 - 5)(4 + 5) f) x6 - y6 = (x4)2 - (y4)2 = (x4 - y4)(x4 + y4)
a) 5x - 20y = 5( x - 4y)
b) 5x(x-1) - 3x(x-1) =2x (x-1)
c) x2 - 9 = x2 - 32 = ( x-3)(x+3)
e) 42-25 = 42 - 52 = ( 4-5)(4+5)= -9
f) x6 - y6 = (x3)2 - (y3)2 = ( x3 - y3 ) ( x3 + y3)
= (x-y) ( x2 + xy + y2 ) ( x+y) ( x2 -xy +y2)
1) x(x - y) + x - y
= x.(x - y) + (x - y)
= (x - y).(x + 1)
2) Câu b sai đề nên mk sửa lại nha
2x3 + x2 - 8x - 4
= (2x3 + x2) - (8x + 4)
= x2.(2x + 1) - 4.(2x + 1)
= (2x + 1).(x2 - 4)
= (2x + 1).(x - 2).(x + 2)
3) 2x2 - 8xy - 5x + 20y
= (2x2 - 5x) - (8xy - 20y)
= x.(2x - 5) - 4y.(2x - 5)
= (2x - 5).(x - 4y)
1) ( x+1) ( x-y)
2) 2x3 + x2 - 8x - 4= 2x3 - 4x2 + 5x2 - 10x + 2x - 4 = 2x2 ( x-2) + 5x( x -2) + 2(x -2)
=( 2x2 + 5x + 2)( x-2)
=( 2x2 + 4x + x + 2)( x-2)
=[ 2x( x+2) + ( x-2)]( x-2)
= ( 2x +1)( x+2)( x-2)
3) 2x2 - 8xy - 5x + 20y
= 2x ( x - 4y) - 5( x-4y)= ( 2x-5)(x-4y)
a)5x-20y
=5x-4*5y
=5(x-4y)
b)x(x-1)-3x(x-1)
=(x-3x)(x-1)
c)x(x+y)-5x-5y
=x(x+y)-5(x+y)
=(x-5)(x+y)
\(5x^2-30x-20y^2+45\)
\(=5\left(x^2-6x-4y^2+9\right)\)
\(=5\left[\left(x-3\right)^2-4y^2\right]\)
\(=5\left(x-3-2y\right)\left(x-3+2y\right)\)